PENINGKATAN KEMAMPUAN KREATIVITAS MELUKIS PADA ANAK USIA 5-6 TAHUN DI PAUD KB AL-ALIF - Nurhasanah, Siti; Yulianti, Puji; Ferianti, Nurdini; Hidjanah, Hidjanah (Jurnal Anak Bangsa, 2026)
This study aims to improve the creativity skills in painting among children aged 5–6 years at PAUD KB Al-Alif through engaging and innovative learning activities. The problem identified in this research is the low ability of children to express their ideas and imagination through painting activities, as shown by the limited variety of shapes, colors, and details in their artwork. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 12 children from Group B at PAUD KB Al-Alif. Data were collected through observation, documentation, and interviews with the classroom teacher. The data were analyzed using a qualitative descriptive technique by calculating the percentage of improvement in children’s creativity skills in each cycle. The results showed a significant increase in children’s creativity in painting from the pre-cycle to the first and second cycles. The children became more confident in combining colors, adding details, and expressing their ideas freely through painting media. Therefore, it can be concluded that well-designed and enjoyable painting activities can effectively enhance the creativity skills of children aged 5–6 years at PAUD KB Al-Alif.